STUDI KELAYAKAN PEMBENTUKAN BUMD ANEKA USAHA DI KABUPATEN SAMOSIR - Munthe, Kornel (Jurnal Manajemen dan Bisnis, 2019)
The purpose of this study is to analyze the feasibility of establishing a Regional Owned Enterprise (BUMD) conducted by the Regional Government of Samosir Regency. The study was conducted in April-August 2018 with data collection techniques in the form of observation, interviews, and documentation. This study uses a quantitative method with three Investment Criteria, namely: Net Present Value (NPV), Net Benefit Cost Ratio (Net B / C), Internal Rate of Return (IRR); and Pay Back Period Analysis (PBP). Based on the results of finanasial analysis, NPV = 49,771,120,662.86; Net B / C = 12.78; IRR = 32%, analysis of Pay Back Period for 4 years. Based on the results of the analysis it can be concluded that the planned establishment of various business enterprises in Samosir Regency is feasible